2018
DOI: 10.3390/ijms19041092
|View full text |Cite
|
Sign up to set email alerts
|

Tau-Induced Pathology in Epilepsy and Dementia: Notions from Patients and Animal Models

Abstract: Patients with dementia present epilepsy more frequently than the general population. Seizures are more common in patients with Alzheimer’s disease (AD), dementia with Lewy bodies (LBD), frontotemporal dementia (FTD) and progressive supranuclear palsy (PSP) than in other dementias. Missense mutations in the microtubule associated protein tau (MAPT) gene have been found to cause familial FTD and PSP, while the P301S mutation in MAPT has been associated with early-onset fast progressive dementia and the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 208 publications
(283 reference statements)
4
49
0
Order By: Relevance
“…approximately 0.7%), while the highest frequency has been observed in PPA, of which the non-fluent type is mainly related to tau deposition. This is in agreement with recent literature data highlighting the role of tau protein in increasing seizure susceptibility and aberrant network excitability[4,44].389A novel finding of the present study is that epilepsy 390 in AD dementia seems to be more drug-responsive391 than epilepsy in non-AD dementias. As discussed 392 before, this result must be taken with caution consid-393 ering the limited number of subjects.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…approximately 0.7%), while the highest frequency has been observed in PPA, of which the non-fluent type is mainly related to tau deposition. This is in agreement with recent literature data highlighting the role of tau protein in increasing seizure susceptibility and aberrant network excitability[4,44].389A novel finding of the present study is that epilepsy 390 in AD dementia seems to be more drug-responsive391 than epilepsy in non-AD dementias. As discussed 392 before, this result must be taken with caution consid-393 ering the limited number of subjects.…”
supporting
confidence: 91%
“…Thus, the role of tau protein seems relevant in determining the increased risk of epilepsy [44]. Indeed, tau pathology is present in AD, but it may also be present in FTD and DLB [44]. The results of the present study seem to suggest a preponderant role of tau protein among all misfolded ones.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Abnormalities in the expression and phosphorylation of tau have also been described in stroke, epilepsy, Alzheimer's disease, frontotemporal dementia, and chronic traumatic encephalopathies . In clinical situations, pathological deposition of hyperphosphorylated tau has been observed in brain samples obtained from surgical resection of epileptic tissue from patients with drug‐resistant chronic TLE . Similarly, brain tissue from other drug‐resistant epileptic conditions such as focal cortical dysplasia also displays hyperphosphorylated tau .…”
Section: Tau‐based Mechanisms In Epilepsymentioning
confidence: 99%
“…Interestingly, the efficacy of various antiepileptic drugs (AEDs) has been tested in epilepsy experimental models and in AD patients, showing a promising function in cognitive impairment prevention (Sánchez et al, 2018). Since tau hyperphosphorylation is the main mechanism responsible for NFT formation, it has been suggested that inhibiting different tau kinases such as CDK5 and GSK3β, involved in tau hyperphosphorylation, could reduce their aggregation (Xie et al, 2017;Holzer et al, 2018), observed in AD (Morris et al, 2011) and epilepsy (Sen et al, 2007;Thom et al, 2011;Tai et al, 2016).…”
Section: Therapeuticsmentioning
confidence: 99%